Early Antibiotic Exposure in Low-Risk Late Preterm and Term Infants - Sonney, Kelley M.; Guindon, Michael G.; Aden, James K.; Drumm, Caitlin M. (American Journal of Perinatology, 2021)
Objective This study aimed to examine the epidemiology of antibiotic exposure and early onset sepsis (EOS) in late preterm and term infants born via cesarean section with rupture of membranes less than 10 minutes.Study design Retrospective review of 1,187 late preterm and term infants born at Brooke Army Medical Center between January 1, 2012 and August 29, 2019. Subjects were assessed for factors related to antibiotic treatment. Statistical analysis was performed to compare infants treated with antibiotics versus observation.Result An early blood culture was obtained from 234 (19.7%) infants; 170 (14.3%) were treated with antibiotics. Infants treated with antibiotics were significantly younger (p < 0.0001), smaller (p < 0.0001), more often diagnosed with respiratory distress (p < 0.0001), and were more frequently admitted to the neonatal intensive care unit (p < 0.0001). There were no cases of culture proven EOS.Conclusion Although this population lacks risk factors for the development of EOS, a significant percentage was treated with antibiotics. This population may benefit from future antibiotic stewardship efforts.Key Points
Keywords: infectious disease; antibiotics; neonatology; retrospective